Effect of timely initiation of breastfeeding on child health in Ghana - Rita Fosu-Brefo; Eric Arthur (Health Economics Review, 2015)
Background: Early initiation of breastfeeding and exclusive breastfeeding practices have been argued to be one of the important ways of ensuring child health. Unfortunately, owing to modernization, most nursing mothers fail to adhere to such practices. This is believed to be a factor contributory to poor child health in Ghana. Thus, this study investigated the effect of timely initiation of breastfeeding on child health in Ghana. Methods: Cross sectional data using secondary data based on the positivism approach to research was employed. The Ordinary least squares and the Instrumental variables approach were used in estimating the effect of breastfeeding and other socio demographic indicators on the health of the child. Data for the study was sourced from the 2008 round of the Ghana Demographic and Health Survey. Results: The results indicate that timely initiation of breastfeeding, both immediately and hours after birth are important factors that influence the child's health. Additionally, factors such as the wealth of the household, mother's education, age and size of the child at birth and age of the mother are important factors that also influence the health of the child in Ghana. Conclusion: The findings imply that efforts should be made on encouraging appropriate breastfeeding practices among nursing mothers to ensure proper child development and growth in Ghana.
Keywords: 330; Breastfeeding; Timely Breastfeeding; Exclusive breastfeeding; Child health